Reaplicação de uma avaliação dos requisitos não-funcionais de acessibilidade, usabilidade e segurança sobre páginas web de universidades para prospecção de alunos no contexto nacional - (:unkn) unknown (Universidade Federal do Pampa, 2025)
This undergraduate thesis presents a methodological approach for evaluating the websites of Brazilian universities, focusing on three key non-functional criteria: accessibility, usability, and security, from the perspective of prospective students. Drawing upon a well-established international study and adapting it to the Brazilian context, the objective was to understand how institutional portals meet users’ needs and to identify opportunities for improvement. The methodology was applied to 65 university websites using globally recognized tools such as WAVE, AChecker, GTmetrix, SSL Labs, and Sucuri SiteCheck, in alignment with international standards like the WCAG 2.1 guidelines. The evaluation revealed widespread deficiencies across all three criteria, particularly in accessibility and cybersecurity, highlighting critical areas that compromise user experience and data protection. Nevertheless, some universities demonstrated exemplary practices, showing a more mature digital presence. The findings supported the development of practical recommendations aimed at enhancing institutional websites, fostering digital inclusion, optimizing user interaction, and ensuring secure digital environments—essential elements for strengthening university visibility and expanding access to higher education.
Keywords: Engenharia de Software; Sites da Web; Acessibilidade; Usabilidade; Universidades brasileiras; Software engineering; Websites; Accessibility; Usability; Brazilian universities; CIENCIAS EXATAS E DA TERRA